Burden of tuberculosis and its association with socio-economic development status in 204 countries and territories, 1990–2019 - Xue, Yi; Zhou, Jie; Wang, Peng; Lan, Jun-hong; Lian, Wen-qin; Fan, Yue-Ying; Xu, Bei-Ni; Yin, Jia-Peng; Feng, Zi-hao; Zhou, Jian; Jia, Chi-Yu (Frontiers in Medicine, 2022)
Background Tuberculosis(TB) always runs in the forefront of the global burden when it comes to infectious diseases. TB, which can lead to quality of life impairment, financial hardship, discrimination, marginalization, and social barriers, is a major public health problem. The assessment of TB burden and trend can provide crucial information for policy decision and planning, and help countries in the world to achieve the goal of sustainable development of ending the epidemic of TB in 2030. Methods All the data are from the Global Burden of Disease 2019(GBD 2019) database, which analyzed the burden trend of age-standardized incidence, DALYs and deaths rate in TB and HIV/AIDS-infected TB over the past 30 years. GBD2019 not only analyzed the burden distribution of TB in 204 countries and main regions of the world but also analyzed the relationship between the burden of global TB and the Socio-demographic Index (SDI). Results The age-standardized incidence, age-standardized disability-adjusted life years(DALYs) and age-standardized deaths rate for HIV-negative TB were 10671.45[9395.60-12194.10], 59042.45[53684.78-64641.53], 1463.62[1339.24-1602.71](95%CI, per 100000 person-years) in 2019, respectively. Age-standardized incidence, age-standardized DALYs and age-standardized deaths rate of HIV/AIDS-XDR-TB (95%CI，per 1000 person-years,) were 2.10[1.51-2.90], 64.23 [28.64-117.74], 1.01[0.42-1.86] respectively. We found that TB is inversely proportional to SDI, the age-standardized incidence, DALYs and deaths rate low burden countries were in high SDI areas, while high burden countries were in low SDI areas. Global TB showed a slow decline trend, but the age-standardized incidence of HIV-positive TB was increasing, and mainly distributed in sub-Saharan Africa. Conclusion Age-standardized incidence, age-standardized DALYs and age-standardized deaths rate of TB is related to SDI, and the burden of low SDI countries is lighter than that of high SDI countries. Without effective measures, it will be difficult for countries around the world to achieve the goal of ending the TB epidemic by 2030. Effective control of the spread of TB requires concerted efforts from all countries in the world, especially in the countries with low SDI, which need to improve the diagnosis and preventive measures of TB and improve the control of HIV/AIDS-TB.